PRADIGMA HUKUM ISLAM DAN HUKUM POSITIF PADA PERKAWINAN DIBAWAH UMUR TANPA IZIN ORANGTUA - Sawaluddin Siregar (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2022)
In this article the author will examine the regulation of underage marriage without parental consent. The author explains through the eyes of Islamic law and positive law. What are the legal consequences for underage marriages without parental consent? While the research method carried out by the author is through a normative juridical approach. That refers to the norms contained in Islamic law and positive law. While the nature of this research is analytical descriptive.The results of the study explain that underage marriage without parental consent in Islamic law and positive law cannot be justified. This means that these two laws prohibit underage marriages from taking place without parental consent. The legal consequences are both null and void. The difference between Islamic law and positive law in terms of marriage is the setting of age limits and the granting of parental consent.